Do gastroenterologists have medical inertia towards coeliac disease? A UK multicentre secondary care study - Hugo A Penny (BMJ Publishing Group, 2021)
Objective This study aimed to assess if there is secondary care medical inertia towards coeliac disease (CD).Design Group (1): Time from primary care presentation to diagnostic endoscopy was quantified in 151 adult patients with a positive endomysial antibody test and compared with 92 adult patients with histologically proven inflammatory bowel disease (IBD). Group (2): Across four hospitals, duodenal biopsy reports for suspected CD were reviewed (n=1423). Group (3): Clinical complexity was compared between known CD (n=102) and IBD (n=99) patients at their respective follow-up clinic appointments. Group (4): 50 gastroenterologists were questioned about their perspective on CD and IBD.Results Group (1): Suspected coeliac patients waited significantly longer for diagnostic endoscopy following referral (48.5 (28–89) days) than suspected patients with IBD (34.5 (18–70) days; p=0.003). Group (2): 1423 patients underwent diagnostic endoscopy for possible CD, with only 40.0% meeting guidelines to take four biopsies. Increased diagnosis of CD occurred if guidelines were followed (10.1% vs 4.6% p<0.0001). 12.4% of newly diagnosed CD patients had at least one non-diagnostic gastroscopy in the 5 years prior to diagnosis. Group (4): 32.0% of gastroenterologists failed to identify that CD has greater prevalence in adults than IBD. Moreover, 36.0% of gastroenterologists felt that doctors were not required for the management of CD.Conclusion Prolonged waiting times for endoscopy and inadequacies in biopsy technique were demonstrated suggesting medical inertia towards CD. However, this has to be balanced against rationalising care accordingly. A Coeliac UK National Patient Charter may standardise care across the UK.